利用實驗及模擬分析來探討脫層複合材料三明治結構之破壞行為 - 蔡佳霖; Tsai Jia-Lin (My University, 2012)
近年來隨著節能減碳的潮流，複合材料三明治結構因具有輕量化、高彎矩強度與高 彎矩剛性，已廣泛地應用於航太、汽車、風力葉片及相關工業。然而三明治結構往往因 為製程的疏失、外力碰撞等，容易產生脫層缺陷，因此本研究主要目的為探討含脫層缺 陷的三明治結構的破壞模式及其強度。當複合材料三明治結構脫層缺陷大於臨界長度 時，三明治結構的主要破壞模式為局部挫曲，因此瞭解複合材料表層厚度、疊層順序以 及芯材的性質對臨界脫層長度的影響將是研究討論的重點。本研究以碳纖維複合材料當 表層，以聚甲基丙烯酰亞胺(polymethacrylimide)發泡材當芯材，並利用在表層與芯材間 埋入離型布，以製作含脫層之複合材料三明治試片。藉由設計含不同脫層長度及不同複 合材料疊層之三明治結構，並施以軸向壓縮負載，以觀察其臨界脫層長度值、破壞模式 及壓縮強度。實驗觀察結果發現，破壞模式首先為脫層區域產生局部挫屈現象，接著為 靠近脫層區域與界面間的芯材破裂。 除了實驗量測觀察破壞模式之外，本研究亦透過有限元素分析(finite element analysis)，進行複合材料三明治結構的破壞模式與強度模擬分析。首先藉由線性挫曲分 析得到含脫層三明治結構之局部挫曲模態，並以此模態當作擾動(perturbation)進行非線 性分析。從非線性應變與負載曲線可預估挫曲負載(buckling load)。此外，藉由最大主軸 應力準則來描述芯材的破壞，經過非線性分析，便可預估整體三明治結構的破壞強度。 最後模擬結果將與實驗獲得的破壞模式及破壞強度進行分析與比較。

With the worldwide tendency of energy conservation, composite sandwich structures with the characteristics of light weight and superlative bending rigidity and strength have been extensively employed in industries, i.e., aerospace, automobile, wind turbine blade. However, because of the manufacturing negligence or low velocity impact, the face/core debonded defects are easily generated within the composite sandwich structure resulting in the substantial reduction of mechanical performance. Thus, understanding the fracture behavior and strength of sandwich structure with debonded defect is an essential task for the industrial application with safety. When the debonded length is greater than the critical length, the failure mode of sandwich structures under compressive loading basically is the local buckling within the debonded region. The effect of composites lay-up sequence, face sheet thickness and core properties on the critical length will be taken into accounted in this study. The debonded composite sandwich specimens were fabricated with graphite/epoxy composite laminates as face sheet and polymethacrylimide form as core. During the fabrication, a release film was artificially embedded between the face sheet and core for the creation of debonded defect. Preliminary experimental observations indicated that the failure is dominated by face sheet local buckling followed by the core failure near the interfacial region. In addition to experimental observation, the finite element analysis was also conducted to characterize the fracture behaviors of the sandwich structures. The buckling mode of the debonded sandwich structure was obtained first from the linear buckling analysis. Subsequently, the buckling mode was regarded as the initial perturbation in the nonlinear analysis, based which the critical buckling load was calculated. Furthermore, in accordance with the maximum tensile stress criterion, the compressive strength of debonded sandwich strength in terms of core failure was predicted accordingly. The simulation results and experimental data will be compared and discussed with each other.
Investigating Failure Behaviors of Debonded Composite Sandwich Structures - Experiments and Simulation
Keywords: 複合材料三明治結構; 脫層缺陷; 破壞行為; 非線性分析; composite sandwich structure; debonded defect; fracture behavior; nonlinear analysis